26.1k views
0 votes
Compute.-2.65 - 16.3 =23.5 + ( -62.74) =

User AVC
by
5.5k points

1 Answer

4 votes

Given:

There are given the expression:


\begin{gathered} -2.65-16.3\text{ and} \\ 23.5+(-62.74) \end{gathered}

Step-by-step explanation:

To find the value of the expression, we need to subtract 16.3 from the -2.65.

Then,


-2.65-16.3=-18.95

And,

In the next expression, we need to add 23.5 with (-62.74).

So,


\begin{gathered} 23.5+(-62.74)=23.5-62.74 \\ =-39.24 \end{gathered}

Final answer:

Hence, the value of the expressions is shown below:


undefined

User AhmedBinNasser
by
5.5k points